Entinostat Improves Motor Function and Neuronal Damage Via Downregulating NLRP3 Inflammasome Activation After Spinal Cord Injury - Dai, Chen; Liu, Bin; Peng, Bibo; Qu, Bo; Lin, Jiezhi; Peng, Baogan; Li, Duan-Ming (Frontiers in Pharmacology, 2021)
Background: Spinal cord injury (SCI), a major public health problem, has no effective treatment. A large number of studies have confirmed histone deacetylases (HDACs) are involved in the physiological processes that occur following SCI. We tried to uncover the potential neuroprotection role of entinostat (a class I HDAC inhibitor) in SCI. Methods: We conducted a preclinical mouse model of SCI and OGD-induced neuronal damage to present the role of entinostat by the analysis of motor function, histopathological damage, local NLRP3 inflammasome activation, and neuronal damage. Results: The results showed that entinotat suppressed HDAC activation (including HDAC 1 and HADC3 expression) and improved the grip strength and BMS score, spinal edema, cell death, and local NLRP3 inflammasome activation in spinal cord following SCI. Furthermore, entinotat significantly increased OGD-inhibited neuronal activity and decreased PI positive cell, HDAC activation, Caspase-1 activation, IL-1β, and IL-18 levels, and NLRP3 expression. Conclusion: Summary, we firstly documented entinotat improved the motor function, histopathological damage, and local inflammatory response and NLRP3 inflammasome activation in spinal cord following SCI and also presented the neuroprotection of OGD-induced neuronal damage via NLRP3 inflammasome. Thus, our study has the potential to reveal the interaction between HDAC and NLRP3 inflammasome in the pathological process as well as SCI, and further promote the clinical indications of HDACi entinotat and clinical treatment for the inflammatory response after SCI.